Samsung Galaxy S6 For Dummies - Hughes, Bill, 1960- (--For dummies., 2015)
Introduces the major features of the Samsung Galaxy S6 smartphone, covering such topics as texting, accessing the Internet, downloading apps, sharing pictures, playing music and videos, using maps, and maximizing shortcuts. --Publisher's description.